Predicting the Effects of Carbapenem/Carbapenemase Inhibitor Combinations against KPC-Producing Klebsiella pneumoniae in Time-Kill Experiments: Alternative versus Traditional Approaches to MIC Determination - Alla V. Filimonova; Maria V. Golikova; Elena N. Strukova; Yury A. Portnoy; Anastasiya A. Kuznetsova; Stephen H. Zinner (MDPI AG, 2021)
Traditionally, the antibacterial activity of β-lactam antibiotics in the presence of β-lactamase inhibitors is determined at the fixed inhibitor concentration. This traditional approach does not consider the ratio of antibiotic-to-inhibitor concentrations achieved in humans. To explore whether an alternative pharmacokinetically based approach to estimate MICs in combinations is predictive of antimicrobial efficacy, the effects of imipenem and doripenem alone and in combination with relebactam were studied in time-kill experiments against carbapenemase-producing Klebsiella pneumoniae. The carbapenem-to-relebactam concentration ratios in time-kill assays were equal to the therapeutic 24-h area under the concentration-time curve (AUC) ratios of the drugs (1.5/1). The simulated levels of carbapenem and relebactam were equal to their concentrations achieved in humans. When effects of combined regimens were plotted against respective C/MICs, a sigmoid relationship was obtained only with MICs determined by pharmacokinetically based method. The effectiveness of both carbapenems in the presence of relebactam was comparable by the results of time-kill experiments. These findings suggest that (1) antibiotic/inhibitor MICs determined at a pharmacokinetically based concentration ratio allow an adequate assessment of carbapenem susceptibility in carbapenemase-producing K. pneumoniae strains and can be used to predict antibacterial effects; (2) in time-kill experiments, the effects of imipenem and doripenem in the presence of relebactam are comparable.